Synthesis of novel 1,4-dihydropyridine and 3,4-dihydropyridone based fluorous cationic amphiphiles for possible transmembrane delivery applications - Šmits, Rufs (Latvijas Universitāte, 2012)
KOPSAVILKUMS. Fluorsaturošu katjono 1,4-dihidropiridīna un 3,4-dihidropiridona amfifīlu sintēze transmembrānu nogādes pētijumiem. Smits R., Dr. Ķīm. Prof. G.W. Buchanan, Dr. Ķīm. Vīgante B., Doktora disertācija , 163 lappuses, 48 attēli, 54 shēmas, 6 tabulas, 266 atsauces. Angļu valodā. 1,4-DIHIDROPIRIDĪNS, 3,4-DIHIDROPIRIDONS, FLUORĒTIE ESTERI, KATJONIE AMFIFĪLI, DNS TRANSFEKCIJA, ZĀĻU PĀRNESE, BROMĒŠANA, OKSIDĒŠANA, HLORO-FORMILĒŠANA, ŪDEŅRAŽA SAITES VEIDOŠANA, PAŠAGREGĒŠANĀS, RENTGENSTARU DIFRAKCIJA, 19F-KMR. Šajā darbā apskatīta 1,4-dihidropiridīnu un 3,4-dihidropiridonu farmakoloģiskā un sintētiskā daudzveidība. Kombinācijā ar garu fluorētu alkilesteru unikālajām īpašībām veidoti iespējami transmembrānu aģenti, risinot līdz šim zināmo sistēmu pašagregēšanās, stabilitātes, toksicitātes un gēnu transfekcijas problēmas ar būtisku priekšrocību – šie nesēji var tikt izsekoti in vivo ar maz agresīvu 19F-magnētisko rezonansi. Darba gaitā izskaidroti vairāki fundamentāli 1,4-dihidropiridīnu un 3,4-dihidropiridonu ķīmijas aspekti, tādi kā stereospecifiska bromēšana, ūdeņraža saites veidošanās un heterocikla oksidēšanās. Lai neapšaubāmi pierādītu sintezēto savienojumu struktūru un iegūtu molekulāro iedarbību datus, izmantota rentgenstruktūras analīze.

ABSTRACT. Synthesis of novel 1,4-dihydropyridine and 3,4-dihydropyridone based fluorous cationic amphiphiles for possible transmembrane delivery applications. Smits R., Dr. Chem. Prof. G.W. Buchanan, Dr. Chem. Vigante B., Doctor’s Thesis , 163 pages, 48 figures, 54 schemes, 6 tables, 266 references. In English language. 1,4-DIHYDROPYRIDINE, 3,4-DIHYDROPYRIDONE, FLUOROUS ESTERS, CATIONIC AMPHIPHILES, DNA TRANSFECTION, DRUG DELIVERY, BROMINATION, OXIDATION, CHLORO-FORMYLATION, HYDROGEN BONDING, SELF-ASSEMBLY, X-RAY DIFFRACTION, 19F-MRI. In this work both the pharmacologically and synthetically versatile 1,4-dihydropyridines and 3,4-dihydropyridones in combination with the unique properties of fluorous long chain alkyl esters allow the generation of novel putative transmembrane delivery agents, addressing the self- assembly, stability, toxicity and gene transfection problems of current systems with the added advantage that these carriers can be tracked in vivo by non-invasive 19F-magnetic resonance imaging. Along the way some fundamental chemistry aspects, such as stereo-specific bromination, hydrogen bonding and oxidation of the 1,4-dihydropyridine and 3,4-dihydropyridone heterocycles are explored. X-ray diffraction is used throughout the work to provide molecular interaction data and unequivocal structural proofs of the synthesized compounds.
Fluorsaturošu katjono 1,4-dihidropiridīna un 3,4-dihidropiridona amfifīlu sintēze transmembrānu nogādes pētījumiem
Keywords: Ķīmija; Analītiskā ķīmija; Analytical chemistry